Government Social Media Existence: Case Study on the Use of Twitter Regional Disaster Management Agency, Province of Yogyakarta Special Region) - Addin Khaerunnisa Juswil; Sanny Nofrima (Journal of Local Government Issues (LOGOS), 2020)
The proper utilization of social media is crucial in terms of disaster management, especially by the government.  One of the government’s method to accelerate the dissemination of information regarding disasters is through official government’s twitter account which has proven to be more effective. This study aims to describe the efforts of the Regional Disaster Management Agency (BPBD) of the Special Region of Yogyakarta in handling crisis through a managed twitter account, namely @pusdalops_DIY.  This research uses descriptive qualitative research method which is carried out by analyzing the twitter using NVIVO 12 Plus data processing software.  The result of this study can be stated that the utilization of the Regional Disaster Management Agency (BPBD) twitter account of the Special Region of Yogyakarta has been effective in disseminating informations and compatible with the main tasks also functions listed in the regional legal basis regarding the Regional Disaster Management Agency (BPBD).  However, it still requires further digitalization in all areas of government to be more integrated and communicative in crisis management.